2002
DOI: 10.1002/jqs.677
|View full text |Cite
|
Sign up to set email alerts
|

Depositional history of the North Taymyr ice‐marginal zone, Siberia—a landsystem approach

Abstract: The sediment-landform associations of the northern Taymyr Peninsula in Arctic Siberia tell a tale of ice sheets advancing from the Kara Sea shelf and inundating the peninsula, probably three times during the Weichselian. In each case the ice sheet had a margin frozen to its bed and an interior moving over a deforming bed. The North Taymyr ice-marginal zone (NTZ) comprises ice-marginal and supraglacial landsystems dominated by thrust-block moraines 2-3 km wide and large-scale deformation of sediments and ice. L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
70
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(72 citation statements)
references
References 57 publications
1
70
1
Order By: Relevance
“…Mo¨ller et al (1999a) and Alexanderson et al (2002) concluded that northern Taymyr were subjected to extensive glaciations in Early to Middle Weichselian times (ca 90-80 and 70-60 ka BP; MIS 5 and 4), but evidence of older glaciations is sparse. Evidence of multiple pre-LGM glaciations is also present on Severnaya Zemlya (Bolshiyanov and Makeyev, 1995).…”
Section: Article In Pressmentioning
confidence: 99%
See 2 more Smart Citations
“…Mo¨ller et al (1999a) and Alexanderson et al (2002) concluded that northern Taymyr were subjected to extensive glaciations in Early to Middle Weichselian times (ca 90-80 and 70-60 ka BP; MIS 5 and 4), but evidence of older glaciations is sparse. Evidence of multiple pre-LGM glaciations is also present on Severnaya Zemlya (Bolshiyanov and Makeyev, 1995).…”
Section: Article In Pressmentioning
confidence: 99%
“…The KSIS recession halted temporarily north of the Byrranga Mountains and constructed the complex North Taymyr ice-marginal Zone (NTZ, Fig. 25B) (Alexanderson et al, 2001(Alexanderson et al, , 2002. Simultaneously an ice-dammed lake was formed between the ice margin and the Byrranga Mountains with meltwater rerouting southwards along the Taymyr River valley, all dated by OSL ages of ca 80 ka BP .…”
Section: Regional Correlationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on geomorphological field work, analyses of aerial photographs and geochronological data, Alexanderson et al (2001Alexanderson et al ( , 2002 argue that LGM ice was present on the northern Taymyr Peninsula (central arctic Siberia). Attempts are being made to trace the LGM boundary east toward the Taymyr Peninsula by use of marine geophysical and geological studies (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Based on geological data Möller et al (1999) and Niessen et al (1999) found no evidence for extended glaciation during the last glacial maximum. Only the northern and northwestern coastal lowlands were covered with a thin ice cap (Alexanderson et al, 2002). Dryness prevented the formation of large ice sheets (Svendsen et al, 1999).…”
Section: Radiocarbon Datesmentioning
confidence: 99%